FINANCIAL RESTATEMENT : DAMPAKNYA TERHADAP REAKSI PASAR - Atasoge, Immawan Azhar Ben; Hendrawan, Diky Angga; Putri, Fani Monada Esaa (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The purpose of this study was to determine the impact of restatement of financial statements on market reactions. This type of research is a quantitative research method, in this study the population used is all companies listed on the Indonesia Stock Exchange non-financial that perform restatement. This study uses annual data on the financial statements of companies that perform restatements in the 2016-2019 period. Regression using OLS (Ordinary Least Square) analysis tool by taking a sample of 21 companies. The results of this study indicate that from the variables of restatement, share ownership, and leverage only share ownership variables have a significant effect on market reaction with a significance value of 0.04 0.05, it can be concluded that there is a significant effect of share ownership on market reaction so that the hypothesis proposed in this research is accepted.